Developmental Features of Reproductive Organs in Viburnum tinus L. - (:unkn) unknown (My University, 2019)
Viburnum tinus, which belongs to Adoxaceae family, is a plant that commonly used inpharmacy and landscape architecture. Flowers located in corymb-type of the inflorescence arewhite, fragrant, hermaphrodite. The development of the flower buds begins with thedifferentiation of the apical meristem as a small bulge. Afterwards, the apical apex isexpanded, flattened and transforms into a floral meristem. Floral meristem cells have largevolume and abundant cytoplasm. Concomitant with the development, firstly five stamenprimordia and then three carpel primordia differentiate from the floral meristem. Anthers aretetrasporangiate. Anther wall is formed by epidermis, endothecium with fibrous thickening,ephemeral middle layer and, plasmodial tapetum. Tapetal cells degenerate at the young pollenstage. Pollen grains are discharged by the opening of stomium. Carpel primordial cellslengthen upwards, merge and form a style above the ovary. An ovule differentiates into eachovarian loculi. But the development continues only in one them and transforms into themature embryo sac. Ovules are unitegmic and tenuinucellate. The style has a transmittingchannel. Stigma is three-lobed and wet typed. The transmitting tissue and stigmatic papillaestart to degenerate after pollination.

Adoxaceae familyasına ait olan Viburnum tinus eczacılık ve peyzaj mimarisinde sıklıkla kullanılan bir bitkidir. Korimbus tip çiçek durumunda bulunan beyaz ve hoş kokulu çiçekler hermafrodittir. Çiçek tomurcuklarında gelişim apikal meristemin küçük bir çıkıntı olarak farklılaşması ile başlar. İlerleyen evrelerde apikal tepe genişleyip düzleşerek floral meristeme dönüşür. Floral meristem hücreleri büyük hacimli ve bol sitoplazmalıdır. Gelişimin ilerlemesi ile beraber floral meristemden ilk önce beş adet stamen taslağı, ardından 3 adet karpel taslağı farklılaşır. Anterler tetrasporangiyattır. Anter çeperi epidermis, fibroz kalınlaşma gösteren endotesyum, kısa ömürlü ara tabaka ve plazmodyal tapetumdan oluşur. Tapetum hücreleri genç polen evresinde körelir. Polen taneleri stomiumların açılması ile doğaya salınır. Karpel taslakları yukarı doğru uzayıp, birleşerek ovaryumun üzerinde stilusu oluşturur. Her ovaryum lokusunda bir tohum taslağı farklılaşır. Ancak tohum taslaklarından sadece bir tanesi olgun embriyo kesesine dönüşür. Tohum taslakları tek integümentli ve tenuinusellat tiptedir. Stilus nakil doku içerir. Stigma üç loblu ve ıslak tiptedir. Stilusun nakil dokusu ve stigma papilleri tozlaşmadan sonra körelmeye başlar.
Viburnum tinus L.’ nin Üreme Organlarının Gelişimsel Özellikleri